Single-input and three-output current-mode biquadratic filters using multiple-output OMAs - Tangsrirat, W.; Unhavanich, S.; Dumawipata, T.; Surakampontorn, W. (My University, 2002)
A novel circuit configuration for the realization of the single-input and three-output (SITO) current-mode biquadratic filters employing only three multiple-output operational mirrored amplifiers (OMAs) is presented. The proposed circuit can simultaneously realize lowpass, bandpass and highpass filter functions at three high-impedance outputs without changing the circuit configuration and elements. Moreover, the resultant current-mode filter provides low passive and active sensitivities, uses of only grounded passive elements and can be orthogonal tuned of the parameters at and Q-factor.
Keywords: Band pass filters; Circuits; Communication industry; Equations; Information technology; Mirrors; Operational amplifiers; Passive filters; Q factor; Transfer functions